Teaching through integration- action research at a private nursing institution in Karachi, Pakistan - Asif, Nimira; Rahim, Shirin; Saleem, Zulekha; Iqbal, Shagufta (Journal of the Pakistan Medical Association, 2024)
Objective: This research aims to explore the outcome of teaching through integration, on nursing students learning using Harden model (1984) of curriculum strategy. Method: The study used action research as a methodology. Two modules of Year II BScN curriculum were taught through integration to 120 students at a private nursing institute in Karachi, Pakistan. The Data was collected from February to May 2018. Four focus group discussions (FGD) of six students each were conducted, before and after module implementation. The data were analysed using Creswell method. Results: The study findings consist of three themes “integration adds to contentment”, “integration carries challenges and “integration supplements teaching learning strategies” with their respective subthemes as Complete connected and comprehensively concise” Integration carries challenges, added burden, and lacked creativity and logistics. Conclusion: The findings show that teaching through integrated modules help students to become focused and responsible learner, optimize understanding of concepts, and strengthen theory practice integration for delivering holistic care. The study recommends to use integration strategy as a step toward for enhanced student learning and better patient outcome. Key words: Education, Nursing, Baccalaureate, Curriculum.